A propensity score-matched comparison of laparoscopic distal versus total gastrectomy for middle-third advanced gastric cancer. (December 2018) - Wang, Wen-Jie; Li, Hong-Tao; Chen, Peng; Yu, Jian-Ping; Jiao, Zuo-Yi; Han, Xiao-Peng; Su, Lin; Tao, Rui-Yu; Xu, Lin; Kong, Yan-Long; Li, Yu-Min; Liu, Hong-Bin
Abstract: Background: The optimal resection extent for middle-third advanced gastric cancer (AGC) still remains controversial. This study aimed to assess the long-term oncologic outcomes of laparoscopy-assisted distal gastrectomy (LADG) versus laparoscopy-assisted total gastrectomy (LATG) for middle-third AGC. Methods: A retrospective cohort study was conducted using data from 464 patients who underwent LADG or LATG between September 2007 and March 2013. Propensity score matching (PSM) were used for reducing the confounding effects to compare the long-term oncologic outcomes between two groups. Cox regression analysis was performed to clarify the prognostic factors. Results: After PSM was performed, a well-balanced cohort of 376 patients (188 LADG and 188 LATG) was further analyzed. Of interest, the LADG group had a significantly shorter operative time (244.6 ± 28.0 vs. 259.1 ± 30.1, P < 0.0001), less operative blood loss (142.9 ± 50.9 vs. 157.8 ± 54.1, P = 0.006), earlier day of first flatus (2.6 ± 0.8 vs. 2.9 ± 0.9, P = 0.014), fewer number of retrieved lymph nodes (36.5 ± 7.9 vs. 41.4 ± 9.8, P < 0.0001), and shorter postoperative hospital stay (9.7 ± 1.3 vs. 10.7 ± 1.4, P < 0.0001) than the LATG group. However, no significant differences were observed in days of eating liquid diet (P = 0.626) and days of eating soft diet (P = 0.353). The incidence of overall and severe postoperative complications (Clavien-Dindo grade ≥ IIIa) following the LADG group were significantly fewer than the LATG group (overall, 24.5% vs. 34.6%, P = 0.032; severe, 4.8% vs. 11.2%, P = 0.022). In addition, the LADG group had significantly more favorable overall survival (OS) and disease-free survival (DFS) rates than the LATG group (5-year OS rate, 55.6% vs. 41.8%, P = 0.002; 5-year DFS rate, 45.9% vs. 32.8%, P < 0.001). In multivariate analyses, resection extent was not an independent prognostic factor for OS and DFS. Conclusions: This PSM cohort analysis has indicated LADG with D2 lymphadenectomy appeared to be safe and reasonable option for patients with middle-third AGC in general. LADG could contribute to improved survival. Graphical abstract: Image 1 Highlights: LADG with D2 lymphadenectomy appeared to be safe and reasonable option for patients with middle-third AGC in general. LADG could contribute to improved survival for middle-third AGC. Resection extent was not an independent predictor for overall and disease-free survival.